2020
DOI: 10.1038/s41598-020-60692-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations in Large-scale Brain Networks and Their Relationship with Sleep Disturbances in the Adolescent Population

Abstract: Although sleep disturbances are highly prevalent in adolescents, neuroimaging evidence on the effects of sleep disturbances on their developing brains remains limited. Therefore, we explored gray matter volumes (GMVs) at the whole-brain level and investigated their relationship to sleep disturbances in a sample of Korean adolescents in the general population. We recruited participants from one middle school and high school. All participants and their legal guardians gave informed consent before participating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 93 publications
2
14
1
Order By: Relevance
“…These ndings also supported the neurobiological model of insomnia (Buysse et al, 2011) that assumed that the speci c brain regions related to sleep include the cortico-limbic circuits, the default mode network, the hypothalamic centers, and the brainstem-hypothalamic arousal centers. Furthermore, in line with our ndings, research suggests that the right PostCG was a main receptive region for external stimuli, which was located in the somatosensory network (SSN) (Joo et al, 2013;Sung et al, 2020). A structural MRI study demonstrated a signi cant reduction in the bilateral PostCG in patients with primary insomnia (Joo et al, 2013), which was related to sleep latency.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These ndings also supported the neurobiological model of insomnia (Buysse et al, 2011) that assumed that the speci c brain regions related to sleep include the cortico-limbic circuits, the default mode network, the hypothalamic centers, and the brainstem-hypothalamic arousal centers. Furthermore, in line with our ndings, research suggests that the right PostCG was a main receptive region for external stimuli, which was located in the somatosensory network (SSN) (Joo et al, 2013;Sung et al, 2020). A structural MRI study demonstrated a signi cant reduction in the bilateral PostCG in patients with primary insomnia (Joo et al, 2013), which was related to sleep latency.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the previous studies revealed that associations with sleep disturbances had decreased volumes in the left IPL (Sung et al, 2020). In contrast, our ndings revealed that the WMV in left IPL was negatively associated with subjective sleep quality and sleep duration.…”
Section: Discussioncontrasting
confidence: 60%
“…Developmentallyspecific brain-sleep relationships could inform the optimal timing of brain and/or sleep-based interventions that promote healthier neurodevelopmental outcomes. Several initial reports have identified ties between diverse gray matter structures and sleep in pediatric populations [41][42][43][44][45][46][47][48] .…”
Section: Many Brain Regions Implicated In Cognitive and Emotional Outmentioning
confidence: 99%
“…All the participants who were engaged in this study met the following criteria: (i) they were capable of understanding and following the instructions and descriptions fully in the present study; (ii) they had no possibility of pregnancy for female before the study; (iii) they were taking no medications that could significantly influence their waking and sleep conditions; and (iv) they had no predicted problems in neuroimaging and psychological tests. Participants with any clear neuropsychiatric history of psychiatric disorders (schizophrenia, bipolar disorder, or pediatric psychosis), developmental disorders (autism or intellectual disabilities), learning disabilities, language impairments, uncorrected sensory impairments, neurological disorders (convulsive disorder), or acquired brain injury (cerebral palsy) were excluded from the analyses (Sung et al, 2020).…”
Section: Participantsmentioning
confidence: 99%
“…The methods have been described in detail in previous studies. (Jung et al, 2019;Sung et al, 2020): (1) the images were manually reoriented to the anterior commissure, (2) the gray matter was segmented using a standard tissue probability map provided by SPM, (3) using the DARTEL procedure, all the images were created as a study-specific template, (4) the images were spatially normalized using the DARTEL template, and the brain size of individuals was adjusted during spatial normalization, and (5) the gray matter was smoothed with a Gaussian kernel of 8 mm full-width at half maximum. After preprocessing, the regional GMV (rGMV) was extracted by averaging the values in the left and right hippocampi, which were defined using the automated anatomical labeling (AAL) atlas.…”
Section: Regional Voxel-based Morphometry Analysismentioning
confidence: 99%